Pазказът на костните останки: два скелета от вкопано жилище № 10, ранносредновековен комплекс Брестница–Полето, Северозападна България - Victoria Russeva; Lyuba Manoilova; Stiliyan Ivanov (Българско е-Списание за Археология)
The skeletal remains of two individuals were discovered in a dugout dwelling (# 10) during rescue excavations of the early medieval metallurgical centre “Brestnitsa–Poleto”, northwestern Bulgaria. While these are not the only skeletons discovered on the site, this find is of note because, unlike other burials excavated nearby, it doe s not represent a regular Christian burial Instead the remains were found on the floor of a housing structure. The radiocarbon dating of the bones indicates they were from the first decade / half of the 9th century. The current paper examines the process of discovering and documenting the skeletal remains in situ. It offers a reconstruction of the situation of the bodies at the time of their death – their positions and location, as well as a possible cause of death. The consequent laboratory analysis presents a detailed report of the individual characteristics of each skeleton starting with age, sex and stature estimation, and a thorough examination of pathological marks and changes, as well as dental and craniometrical indexes where the condition of the bones allowed a reconstruction.